Brownie & Pearl grab a bite - Rylant, Cynthia; Biggs, Brian (New York : Beach Lane Books, 2011)
A little girl and her cat enjoy their lunch of cheese, apples, crackers, and milk in different ways.
Kirkus Review
School Library Journal
Kirkus Review, July 2011
School Library Journal, August 2011
0.8
Preschool
Keywords: Cats -- Juvenile fiction; Food habits -- Juvenile fiction; Luncheons -- Juvenile fiction; Cats -- Fiction; Food habits -- Fiction; Luncheons -- Fiction; Cats -- Fiction; Eating customs -- Fiction; Luncheons -- Fiction; Picture books for children